Peningkatan Hasil Belajar Pendidikan Jasmani Melalui Metode Pembelajaran Penugasan Dalam Materi Pembelajaran Senam Lantai Pada Siswa Kelas XI IPS 2 SMAN 2 Kota Sukabumi - Firman Maulana; Asep Odang SA (utile: Jurnal Kependidikan, 2019)
This study aims to determine the assignment learning method can improve physical education learning outcomes in floor gymnastic learning material in class XI IPS 2 students at SMAN 2 Sukabumi.This study used the class action research method (PTK) which was conducted in one cycle for students of class XI IPS 2 in SMA N 2 Sukabumi City, amounting to 34 students from January 24, 2019 to March 21, 2019.Student learning outcomes were assessed from all three aspects, the first psychomotor aspects with an average value of 23.91, for cognitive assessment with an average of 9.26, and for affective assessment with an average of 28.55, as well as the results of classroom observations for lecturers PDS and physical education teachers with an average score of 71.12, while the results of classroom observations for XI IPS 2 students have an average of 51.75.The results of this study indicate that the assignment learning method increased in the affective aspects of floor gymnastic learning which had an impact on sense of responsibility, cooperation, and mutual help on assignments given during floor gymnastics to class XI IPS 2 students of SMA N 2 Sukabumi City seen from increasing the affective value of the front bolster material, back rolling and wheel / propeller.